Kromosomer – an experience in shared creative work and expression - Sousa, Catarina Carneiro de (2022)
Kromosomer is a storytelling performance that interacted with digital, virtual and social media, using characters from Norwegian legends as a motto to raise questions on alterety: the "other, the not normal, the one that looks "different", which we want to distance ourselves from. The abject, something outside the subject and object, prior to the subconscious, something primitive that has not yet manifested itself symbolically.